Region-specific metabolic alterations in the brain of the APP/PS1 transgenic mice of Alzheimer's disease - González-Domínguez, Raúl; García-Barrera, Tamara; Vitorica, Javier; Gómez-Ariza, José Luis (Biochimica et biophysica acta, 2014)
Alzheimer's disease (AD) is the most common neurodegenerative disorder worldwide, but its etiology is still not completely understood. The identification of underlying pathological mechanisms is becoming increasingly important for the discovery of biomarkers and therapies, for which metabolomics presents a great potential. In this work, we studied metabolic alterations in different brain regions of the APP/PS1 mice by using a high-throughput metabolomic approach based on the combination of gas chromatography–mass spectrometry and ultra-high performance liquid chromatography–mass spectrometry. Multivariate statistics showed that metabolomic perturbations are widespread, affecting mainly the hippocampus and the cortex, but are also present in regions not primarily associated with AD such as the striatum, cerebellum and olfactory bulbs. Multiple metabolic pathways could be linked to the development of AD-type disorders in this mouse model, including abnormal purine metabolism, bioenergetic failures, dyshomeostasis of amino acids and disturbances in membrane lipids, among others. Interestingly, region-specific alterations were observed for some of the potential markers identified, associated with abnormal fatty acid composition of phospholipids and sphingomyelins, or differential regulation of neurotransmitter amino acids (e.g. glutamate, glycine, serine, N-acetyl-aspartate), not previously described to our knowledge. Therefore, these findings could provide a new insight into brain pathology in Alzheimer's disease. [Display omitted] •The APP/PS1 mouse exhibits an abnormal neurochemical profile compared to controls.•These metabolic perturbations are widespread, affecting multiple brain regions.•Region-specific alterations were observed for some of the markers identified.•Metabolic changes enabled the elucidation of underlying pathological mechanisms.